The Academic Success of Computer Science Students in the COVID-19 period - Brandao, Pedro; Joaquim, Vitor (International Journal of Scientific Research and Management (IJSRM), 2022)
Comparative study of students' evaluation in technological degrees, between COVID-19 and the homologous period before COVID-19. The study covers a wide range of students, all from the computer science areas. It is intended to verify whether the transition to the 100% online class model impacted student success and, if so, what type of impact.